PENGARUH MODAL KERJA, KEPEMILIKAN MANAJER DAN PERTUMBUHAN PENJUALAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERCATAT DI BEI SELAMA PERIODE 2015-2017 - Putri, Laily Mandala; Wuryani, Eni (Jurnal Akuntansi AKUNESA, 2020)
This study aimsd to know the effect of working capital, managerial ownership and sales growth on financial performance. The population used is all companies listed on the Indonesia Stock Exchange. Based on quantitative research methods with a purposive sampling technique, there were 48 companies that became research samples during period 2015-2017. Data analysis method used is multiple linear regression. The results of research showed that working capital and sales growth has an effect on financial performance, while managerial ownership has no effect on financial performance.